2011
DOI: 10.1210/jc.2011-0632
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Determined Dosage of Follicle-Stimulating Hormone (FSH) Affects Male Reproductive Parameters

Abstract: Context:The detailed role of FSH in contributing to male testicular function and fertility has been debated. We have previously identified the association between the T-allele of the FSHB promoter polymorphism (rs10835638; G/T, −211 bp from the mRNA start) and significantly reduced male serum FSH.Objective:In the current study, the T-allele carriers of the FSHB −211 G/T single nucleotide polymorphism represented a natural model for documenting downstream phenotypic consequences of insufficient FSH action.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
6
41
0
Order By: Relevance
“…This was then amply confirmed in German and Italian men (62,63). In accordance with the epidemiological and in vitro data reported above, homozygous carriers of the minor allele represent only 1.5% of men with normal semen parameters but have serum FSH levels which are about 25% lower than homozygous, major allele carriers (11,62,64). In addition, this polymorphism is associated with lower testicular volume, lower sperm count, lower testosterone, and higher LH serum levels (11,62,63,64,65).…”
Section: Fshbsupporting
confidence: 74%
See 1 more Smart Citation
“…This was then amply confirmed in German and Italian men (62,63). In accordance with the epidemiological and in vitro data reported above, homozygous carriers of the minor allele represent only 1.5% of men with normal semen parameters but have serum FSH levels which are about 25% lower than homozygous, major allele carriers (11,62,64). In addition, this polymorphism is associated with lower testicular volume, lower sperm count, lower testosterone, and higher LH serum levels (11,62,63,64,65).…”
Section: Fshbsupporting
confidence: 74%
“…One study showed that patients with at least one FSHR c.2039AOG G allele had a significant increase in total sperm count after 3 months of treatment with rFSH (150 IU/thrice per week) (83). Another study considered the FSHB K211GOT genotype and showed that TT homozygotes, representing 25% of men with oligozoospermia and low FSH levels, could significantly benefit from FSH treatment (64). No study has addressed the combination of the two genotypes …”
Section: Pharmacogenetic Studies In Menmentioning
confidence: 99%
“…Several studies have suggested that hormone levels may be heritable and may predispose individuals to subclinical HH [23,[83][84][85][86][87]. Additionally, polymorphisms in the androgen receptor and trinucleotide repeats may account for a large proportion of the subclinical HH.…”
Section: Discussionmentioning
confidence: 99%
“…SNP‐trait association tests were performed using linear regression, assuming an additive genetic model. In the Baltic cohort, regression testing was adjusted for age, BMI, smoking status, recruitment centre; hormone measurements were additionally corrected for blood sampling hour, and semen parameters were corrected for ejaculation abstinence period according to the analysis settings described previously (Table S1; Grigorova et al ., 2011). In the study group of Estonian idiopathic infertility patients, adjustment for age was applied for all parameters and abstinence period was used as an additional confounder in association tests with semen parameters.…”
Section: Methodsmentioning
confidence: 99%